The role of gfi1b in zebrafish thrombopoiesis - O'Hare, Conor (2019)
gfi1b is a member of the gfi1 family of genes which encode zinc finger transcriptional repressors that are involved in regulating haematopoiesis. In mammals it has been shown that the loss of gfi1b function causes defects in megakaryocyte maturation, leading to the inability to produce platelets. Thrombocytes are the functional equivalent of mammalian platelets in zebrafish. Using a homozygous gfi1b knockout allele and cd41:GFP marker transgene we examined thrombocyte development in gfi1b mutant and gfi1b wt fish. Here we show that gfi1b is not required for initial thrombocyte specification in zebrafish as GFP +ve cells are present in the CHT at 3dpf in gfi1b mutant and gfi1b wt fish. Our data suggests that gfi1b is required for full maturation of thrombocytes as analysis by flow cytometry indicated a distinct reduction in GFP fluorescence when gfi1b function was removed compared to gfi1b wt embryos. We have also found that there is a delay in thrombocytes entering the circulation in gfi1b mutants with GFP +ve cells beginning to be seen in circulation at 18 days post fertilisation (dpf), in contrast to gfi1b wt embryos which have GFP +ve cells in circulation from 3dpf. This phenotype is similar to one found in gfi1aa and gfi1b doubly knockout mutant fish where primitive red blood cells (prRBCs) are delayed by several days before going into circulation. We also observed that the loss of gfi1b does not interfere with the process of haematopoietic stem cells (HSCs) migrating from the caudal haematopoietic tissue (CHT) to seed the kidney marrow. We conclude that gfi1b is responsible for regulating the rate of thrombocyte maturation in zebrafish.